Banda Aceh as a Civilized City Model: (A Theory and Reality Study) - Manan, Abdul; Muhazar, Muhazar; Syahputra, Rahmad; Salasiyah, Cut Intan (SCAD Independent, 2020)
This research studied the City Government’s endeavor of Banda Aceh to make the city as a civilized city model. Describing the efforts and constraints faced by the government, revealing responses of local citizens, and defining the present conditions of the city became the objective. A qualitative approach covering field observations, documents, and interviews, was applied and followed by data reduction, data display, and concluding. By involving related stakeholders, the new government duo headed by Aminullah Usman and Zainal Arifin has extended the Medium-term Development Plan to realize anew Long-term Development, Land Use, and Area Plan. Nevertheless, a lack of participation in the implementation of sharia appeared, less than optimal governance systems and uneven economic empowerment. Those generated varied responses from the lower, middle, and upper-class citizens. Therefore, to bring the glory of Banda Aceh, the duo has launched the concept of Banda Aceh the Brilliant City.